2022
DOI: 10.1038/s41598-022-25122-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial properties of a multi-component alloy

Abstract: High traffic touch surfaces such as doorknobs, countertops, and handrails can be transmission points for the spread of pathogens, emphasizing the need to develop materials that actively self-sanitize. Metals are frequently used for these surfaces due to their durability, but many metals also possess antimicrobial properties which function through a variety of mechanisms. This work investigates metallic alloys comprised of several metals which individually possess antimicrobial properties, with the target of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…14 Alamdari et al 9 reported the substantial 98.5% antibacterial efficacy of the TiZrTaNbWAg polyelemental film against Escherichia coli (E. coli) bacteria. Murray et al 10 reported the 6.4 log reduction of the double-stranded deoxyribonucleic acid (DNA) activity of E. coli bacteria after interacting with the CoCuAgNiSi polyelemental film. Chen et al 15 evaluated 97.45% antibacterial efficacy of the CrFeNiCuSi polyelemental alloy against E. coli bacteria by exhibiting synergistic activity of multiple metal cations.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Alamdari et al 9 reported the substantial 98.5% antibacterial efficacy of the TiZrTaNbWAg polyelemental film against Escherichia coli (E. coli) bacteria. Murray et al 10 reported the 6.4 log reduction of the double-stranded deoxyribonucleic acid (DNA) activity of E. coli bacteria after interacting with the CoCuAgNiSi polyelemental film. Chen et al 15 evaluated 97.45% antibacterial efficacy of the CrFeNiCuSi polyelemental alloy against E. coli bacteria by exhibiting synergistic activity of multiple metal cations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Polyelemental materials are an emerging class of materials with vast compositional space that can be tuned to promote the synergistic properties of alloyed materials for various applications ranging from clean energy , to healthcare , and structural materials. , Recent studies show the potential of polyelemental materials for biological applications such as antibacterial agents or medical implants. , Polyelemental alloys possess excellent mechanical and chemical stability attributing to their configurational mixing entropy . Alamdari et al reported the substantial 98.5% antibacterial efficacy of the TiZrTaNbWAg polyelemental film against Escherichia coli (E.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation